DOP24 Crohn's Disease fistula show skewed lymphoid/myeloid balance, altered myeloid cell profiles and high TNF-α expression. (27th May 2021) - Becker, M; de Krijger, M; Bemelman, W; de Jonge, W; Buskens, C; Wildenberg, M
Abstract: Background: A fistula is an abnormal tract connecting two epithelialized surfaces, for example the intestine and the skin. Perianal fistula are a common complication of patients suffering Crohn's Disease (CD), but also occur in non-IBD patients in the form of cryptoglandular fistula. Around one third of all CD patients develop fistula at some point during their disease course. Fistula are often refractory to therapy, due to poor wound healing responses. In contrast, cryptoglandular fistula often respond to standard therapy. The biological background of this difference is unknown, and comparative studies between the two groups are lacking. The aim of this study was to characterize the cellular composition in fistula tracts of CD and cryptoglandular patients. Methods: Curettage material of perianal fistula tracts was obtained during surgical intervention from patients with CD (n=15) and cryptoglandular fistulas (n=5). Single-cell suspensions were stained with a 35-antibody panel, focusing on myeloid and T-cell markers and were analyzed using mass cytometry (CyTOF). To visualize macrophages in the fistula tract we performed in situ hybridization with CD68 and TNF-α. Results: The main cellular component of both fistula tracts consisted of CD66a+ granulocytes (64 +/- 24%). However, the remaining mononuclear compartment differed significantly between Crohn and cryptoglandular fistula. In CD, the majority was of lymphoid nature (CD3+ T cells 57 +/-21%, CD19+ B cells 14 +/-15%), while in cryptoglandular tracts, the majority consisted of myeloid origin (61+/- 15%). Within the T cell compartment, the majority of cells was CD45RO+, indicating activation. Presence of a seton increased the proportion of CD45RO+ T cells, in particular in CD4+ cells. In the myeloid compartment, CD14high/HLA-int monocytes, CD14int/HLA-high inflammatory macrophages and CD14high/CD163+ resident macrophages were identified. Interestingly, CD patient samples contained less monocyte-like cells, and substantially more resident macrophages compared to cryptoglandular samples. This feature tended to be even more enhanced in the presence of a seton, although this did not reach statistical significance. In situ hybridization showed a high production of TNF-α in epithelial-like cells in fistula tract of Crohn's disease patients, but not in macrophages. Conclusion: Despite granulocytes being the main contributor to the cellular composition of fistula tracts, striking differences were found between Crohns and cryptoglandular fistula, both in lymphoid/myeloid balance, and in the presence of resident macrophages. We also showed that epithelial-like cells in Crohns's disease fistula tracts produce high amounts of TNF-α. These differences may contribute to the lack of response to therapy in CD.